2010
DOI: 10.1152/jn.01121.2009
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Ca2+Activates a Cation Current inAplysiaBag Cell Neurons

Abstract: Ion channels may be gated by Ca(2+) entering from the extracellular space or released from intracellular stores--typically the endoplasmic reticulum. The present study examines how Ca(2+) impacts ion channels in the bag cell neurons of Aplysia californica. These neuroendocrine cells trigger ovulation through an afterdischarge involving Ca(2+) influx from Ca(2+) channels and Ca(2+) release from both the mitochondria and endoplasmic reticulum. Liberating mitochondrial Ca(2+) with the protonophore, carbonyl cyani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 95 publications
1
21
0
Order By: Relevance
“…; Hickey et al . ; White & Magoski, ). There was an ∼200% increase in the current during the step at peak I OAG vs .…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…; Hickey et al . ; White & Magoski, ). There was an ∼200% increase in the current during the step at peak I OAG vs .…”
Section: Resultsmentioning
confidence: 98%
“…; Hickey et al . ; White & Magoski, ), OAG increases membrane conductance and reverses close to −20 mV, suggesting it too carries cations non‐selectively. In addition, activation of I OAG also causes a marked elevation in [Ca 2+ ] i , punctuated by sharp increases in the fura ratio synchronized with large spikes of I OAG .…”
Section: Discussionmentioning
confidence: 98%
“…Carbonyl cyanide p-trifluoromethoxyphenylhydrazone (FCCP; 21857, Sigma-Aldrich), carboxyeosin (C-22803, Invitrogen), ryanodine (559276, Calbiochem, San Diego, CA), and cyclopiazonic acid (CPA; C1530, Sigma-Aldrich or 239805, Calbiochem) all required DMSO as a vehicle. The maximal final concentration of DMSO was 0.5% (vol/vol), which in control experiments as well as prior work from our laboratory had no effect on membrane potential, various macroscopic or single-channel currents, resting intracellular Ca 2ϩ , or Ca 2ϩ transients evoked by a train of action potentials (Gardam et al 2008;Geiger and Magoski 2008;Hickey et al 2010;Hung and Magoski 2007;Kachoei et al 2006;Lupinsky and Magoski 2006;Tam et al 2009Tam et al , 2011. Tetraphenylphosphonium chloride (TPP; 218790, Sigma-Aldrich) was prepared in water.…”
Section: Reagents and Drug Applicationmentioning
confidence: 99%
“…Prior work has established that the mitochondria contribute prominently to both Ca 2ϩ removal and CICR after voltage-gated Ca 2ϩ influx in cultured bag cell neurons (Geiger and Magoski 2008;Groten et al 2013). Consequently, the mitochondria are implicated in sustaining peptide release and membrane excitability during the afterdischarge (Fisher et al 1994;Hickey et al 2010Hickey et al , 2013Michel and Wayne 2002;Wayne et al 1998).…”
mentioning
confidence: 99%
“…The maximal final concentration of DMSO or ethanol ranged from 0.05 to 0.5% (vol/vol), which in control experiments had no effect on holding current, membrane conductance, or junctional current. Prior work from our laboratory has found that these vehicles do not alter bag cell neuron macroscopic or single-channel currents, membrane potential, membrane capacitance, or intracellular Ca 2ϩ (Magoski et al 2000;Magoski and Kaczmarek 2005;Kachoei et al 2006;Lupinsky and Magoski 2006;Hung and Magoski 2007;Gardam et al 2008;Geiger and Magoski 2008;Tam et al 2009Tam et al , 2011Hickey et al 2010Hickey et al , 2013. We also attempted to employ carbenoxolone (C4790; Sigma-Aldrich) but were unable to dissolve it into nASW from either a DMSO-or ethanol-based stock.…”
mentioning
confidence: 97%